Lesbianidades e as referências legitimadoras da sexualidade - Toledo, Lívia Gonsalves [UNESP]; Teixeira Filho, Fernando Silva [UNESP] (My University, 2010)
This article is part of a master's degree dissertation that studied the way as stigmas and stereotypes regarding lesbianity influence the life, in the sphere of the sexuality, of women that denominate themselves as lesbians, resident in a city in the interior of the State of São Paulo. The stigma here analyzed is that lesbians are women that frustrated with men. We tried to show, through the narratives of the research s participants and basing on gender and feminist studies, how the heteronormativist system naturalizes the masculinity to the men and the sexuality in the masculinity, and how it legitimates speeches about lesbian woman through the heterosexual referential. Also, we tried to show some strategies of the biopoder for the maintenance of that system and, starting from interviews in depth, we presented how the participants of the research (lesbian women) make speeches on that stigma and how they re-significate it through their own narratives. That research was financed by Fundação de Amparo à Pesquisa do Estado de São Paulo FAPESP, and accomplished by the Pos-Graduation Program of the Universidade Estadual Paulista Campus of Assis-SP.Key words: Gender. Sexuality. Lesbianity. Heteronormativity.

Este trabalho é parte de uma dissertação de mestrado que estudou o modo como estigmas e estereótipos a respeito da lesbianidade influenciam a vida, na esfera da sexualidade, de mulheres que se autodenominam lésbicas, residentes em uma cidade do interior do Estado de São Paulo. O estigma aqui analisado é que lésbicas são mulheres que se frustraram com homens. Tentamos mostrar, a partir das narrativas das participantes da pesquisa e baseando-nos nos estudos de gênero e feministas, como o sistema heteronormativo naturaliza a masculinidade aos homens, a feminilidade às mulheres, e legitima os discursos sobre as lesbianidades a partir do referencial da heterossexualidade. Buscamos mostrar, ainda, algumas estratégias do biopoder para a manutenção desse sistema e, a partir de entrevistas em profundidade, apresentamos como as participantes da pesquisa (mulheres que se autodenominam lésbicas) se articulam com esse estigma e o re-significam a partir de suas próprias narrativas. Essa pesquisa foi financiada pela Fundação de Amparo à Pesquisa do Estado de São Paulo FAPESP, e realizada pelo Programa de Pós-Graduação da Universidade Estadual Paulista Campus de Assis-SP.Palavras chave: Gênero. Sexualidade. Lesbianidade. Heteronormatividade.
Lesbianities and the legitimator references of sexuality
Keywords: Gender; Sexuality; Lesbianity; Heteronormativity; Gênero; Sexualidades; Lesbianidade; Heteronormatividade compulsória